(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
T.V.Sambasivam pillai, the acclaimed author, of the Cyclopaedic Dictionary is well known in the field of Indian Medicine especially Siddha medicine. Cyclopaedic Dictionary is considered as one of the great treasures of the Siddha system. Neither did he possess a basic medical degree nor he hailed from a family with medical background but his depth of knowledge in the Siddha system is highly commendable. He spent his entire life contributing and deciphering the ancient literatures of the Siddha system. This article is a tribute to his dedication, aspiration, devotion, and sacrifice for the Siddha system of Medicine and aids in highlighting the excerpts of the Cyclopaedic Dictionary.